Consumer Protection In Malaysian E-Commerce - Sarabdeen , Jawahitha (2006)
E-commerce is changing the way consumers and businesses relate to each other both domestically and internationally. Consumer today can access and purchase goods, services and information from across and around the world at the click of a button. To take full advantage of this opportunity, the consumer confidence needs to be built in matters such as contract, use of personal information, quality assurance of goods and services and availability of redress if things go wrong. Both developed and developing countries adopted measures to built trust and confidence by enacting consumer laws ensuring consumer protection.